Improved spatial learning and memory performance following Tualang honey treatment during cerebral hypoperfusion-induced neurodegeneration - Saxena, Anil Kumar; Phyu, Hnin Pwint; Al-Ani, Imad Matloub Dally; Syed Ahmad, Pakeer Oothuman (Open Access Text ( OAT), 2016)
Honey has shown potential therapeutic properties in traditional medicine. This study investigated the cognition enhancing potential of Tualang honey in chronic cerebral hypoperfusion- induced neurodegeneration by permanent bilateral common carotid arteries ligation (2 vessels occlusion- 2VO) in rats. Previous studies have shown that rats subjected to 2VO (2 vessel occlusion) experienced cognitive deficits, oxidative stress and neuronal injury in the hippocampus of the brain. We studied the effect of Tualang honey on learning and memory using the Morris water maze (MWM) in rats. Rats were randomly divided into four groups (n=10); Sham control, untreated 2VO (2VO), honey treated 2VO (2VO+H) and honey treated group (H). Each group was again divided into two subgroups (n=5): one for long term memory assessment and another for short term memory and relearning tasks. After 10 weeks of treatment, all rat groups were tested for cognitive assessment by MWM (Morris water maze). 2VO+H rats had better spatial learning and memory performance than untreated 2VO rats in MWM tasks (p<0.05). However, there was no significant difference between Sham rats and H group rats (p>0.05). This study shows that Malaysian Tualang honey might have therapeutic potential for the treatment of chronic cerebral hypoperfusion related neurodegenerative disorders such as Alzheimer’s disease (AD) in which cognitive impairment is profound.